A CASE REPORT OF THE TEMPORAL BONE METASTASIS OF LUNG CARCINOMA - Yoshiura, Kouji; Otsuka, Kouji; Funasaka, Sotaro; Simoda, Katsuhiro; Hiraide, Fumihisa (JIBI INKOKA TEMBO, 1997)
A 34-year-old man complained of facial nerve palsy in the right side and hearing loss in the right ear. He had been treated with chemotherapy and operation for lung carcinoma. The audiogram showed a profound sensorineural hearing loss in the right ear. No widening of the internal auditory canal was observed by X-ray examination. However MRI revealed a large mass occuping the petroapical region. The right internal auditory canal was enhanced by gadolinium. 99 mTc-HMDP scintigram revealed multiple gatherings in the whole body and also at petroapical region. The patient was diagnosed as having a temporal bone metastasis of lung carcinoma. The authors thought that the spread of tumor into the internal auditory canal was caused by meningeal carcinomatosis.